PERSPEKTIF HUKUM DALAM SISTEM PELAYANAN BEA & CUKAI TERHADAP BARANG IMPOR DI KOTA PAREPARE - Asram A.T. Jadda, Asrul Hidayat, Zulfiqri Arifai (FAKULTAS HUKUM UM PAREPARE, 2023)
This study aims to determine the Legal Perspective in the Customs & Excise Service System for Imported Goods and to find out the Constraints faced by Customs & Excise in carrying out Control of Imported Goods. This research was carried out at the TMPC Customs & Excise Supervision and Service Office in Parepare City. This research uses a descriptive-qualitative method with a normative-empirical approach. The data collection techniques in this study are by means of literature, interviews and documentation. The results of this study indicate that the Customs Service in carrying out Service and Supervision of imported goods always adheres to or is in accordance with the Customs Law, and has been implemented when imported goods enter the territory of Parepare city. The obstacles faced by Customs & Excise in carrying out Supervision are the breadth of the area and also the lack of Personnel (HR) from Customs & Excise so that carrying out Supervision is still difficult.